Prediction of body fat increase from food addiction scale in school-aged children and adolescents: A longitudinal cross-lagged study - Wang, Dan; Zhou, Hui; Hu, Yuzheng; Che, Yanfen; Ye, Xian; Chen, Junqing; Fu, Junfen; Xu, Hongzhen (Frontiers in Public Health, 2023)
Objective: Food addiction (FA) is associated with a higher body mass index z-score (BMIZ) in children and adolescents; however, whether these two aspects evolve interdependently remains unknown. This study aimed to address this question using a cross-lagged experiment. Methods: Weight status, including BMIZ, fat content (FC), and visceral fat level (VFL), was determined in 880 children and adolescents (mean age = 14.02 years [range = 8.83–17.52 years]) at two-time points with an interval of 6 months. FA was characterized using the Chinese version of the dimensional Yale Food Addiction Scale for Children 2.0. Furthermore, FC and VFL were measured using direct segmental multifrequency bioelectrical impedance analysis at each time point. Results: Higher FA was associated with increased BMIZ, FC, and VFL (P < 0.05). FA at T0 could predict FC at T1 (P < 0.05). The characteristics of females, primary students, and living in urban areas may aggravate the adverse effect of FA on weight status over time and age, particularly the increased VFL in participants aged >14 years. Conclusions: Children and adolescents with a high FA level were at risk for weight gain attributed to increased FC, and the adverse effect could be aggravated with time and age. Novel FA-targeting interventions may help mitigate the risk of getting obesity.